Effect of graded levels of formic acid on gut microflora count, serum biochemical parameters, performance and carcass yield of broiler chickens - PANDA, A K; RAJU, M V L N; RAO, S V RAMA; SUNDER, G SHYAM; REDDY, M R (The Indian Journal of Animal Sciences, 2011)
The influence of formic acid (FA) supplementation in diets on the performance of broiler chicken was evaluated. Control starter (0â€“3 wk) and finisher (4â€“6 wk) diets were formulated to contain 2900 kcal ME/kg with 22% CP and 3000 kcal ME/kg with 20% CP, respectively. In addition, 6 experimental diets were constituted with the inclusion of 50 g antibiotic (furazolidone)/ quintal or FA at 0.2, 0.4, 0.6, 0.8 or 1.0% to the control diet. Each diet was offered ad lib. in cages to 6 replicates of 6 chicks each from day-old to 6 wk of age. Formic acid at 0.6% of the diet significantly improved the body weight gain and feed conversion ratio, which was as par with the antibiotic supplemented group. Increasing the concentration of FA from 0.6 to 0.8% further improved both the above parameters with no subsequent improvement thereafter. The digestibility of crude protein and calcium and their concentrations in serum, and dressed yield were significantly higher and abdominal fat content was lower in the dietary groups that contained 0.6 to 1% FA. Dietary addition of FA at 0.6% and above reduced the Escherchia coli counts in crop but not in the small intestine and caecum. Higher concentration of FA (0.8% and 1%) was more beneficial in reducing the Escherichia coli counts in small intestine (SI) and caecum and was as par with the antibiotic group. From this study, it is concluded that 0.8% formic acid in the diet of broiler chickens elicited optimum performance and provided better results than antibiotic (furazolidone).Â